VERBAL INTERACTION IN ENGLISH CLASSROOM USING FLANDERS INTERACTION ANALYSIS CATEGORIES SYSTEM (FIACS) - Fitri Mardiana; Zainuddin Zainuddin; Johannes Jefria Gultom (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2018)
The thesis deals with the dominant category used by teacher and the students during English classroom interaction, and the percentage of teacher’s talk and students’ talk during English classroom interaction using Flanders Interaction Analysis Categories System (FIACS). Moreover, this study used descriptive qualitative design .The data of this study were utterances between English teacher and students during English classroom in XI-2 IPA of SMA Negeri 11 Medan.The instruments for data collection were observation tally sheet and video recording. The result showed all of the categories used in the teaching and learning process. It found from the percentage of all categories , the dominant category used by the teacher was Giving Direction (40.41% ). In the other hand the dominant category used by students was Student Talk-Response (57.60%). In addition, the percentage of Teacher Talk was 59.76%, and the percentage of Student Talk  was 36.72% during classroom interaction in English lessons .It showed, the teacher more active and dominant talking than the students during verbal classroom interaction.Key words: Verbal Classroom Interaction, Teacher Talk, Student Talk, Flanders Interaction Analysis Categories System